Abnormalities in Puberty 2005
DOI: 10.1159/000084093
|View full text |Cite
|
Sign up to set email alerts
|

Puberty and Fertility in Congenital Adrenal Hyperplasia

Abstract: Congenital adrenal hyperplasia (CAH) is a disorder of adrenal steroid synthesis. The symptoms and signs of CAH depend on the degree of enzyme deficiency; severe salt-wasting (SW) form, less severe simple virilizing (SV) form and mild nonclassic (NC) form. In this paper, puberty and fertility in CAH are discussed. The time of onset of puberty and progress of pubertal development is quite normal, except in NC patients (earlier). Also the age of menarche in CAH girls is normal, but it can depend on the level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
2
23
0
7
Order By: Relevance
“…The high expression of DLK1 in TART may suggest that these nodules develop from an immature or even fetal cell type. The similar expression profiles of TART and fetal (this study) and adult (21) adrenal cortical cells lend support to the hypothesis that TART derives from an adrenal-like cell type, possibly misplaced in the gonad during early embryonic development (6,7,8). Moreover, the absence of INSL3 expression in TARTs is at odds with the development of TART from a cell population within one of the LC lineages.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The high expression of DLK1 in TART may suggest that these nodules develop from an immature or even fetal cell type. The similar expression profiles of TART and fetal (this study) and adult (21) adrenal cortical cells lend support to the hypothesis that TART derives from an adrenal-like cell type, possibly misplaced in the gonad during early embryonic development (6,7,8). Moreover, the absence of INSL3 expression in TARTs is at odds with the development of TART from a cell population within one of the LC lineages.…”
Section: Discussionsupporting
confidence: 76%
“…TART is not an invasive tumour, but may eventually cause a testicular degeneration by obstruction of the rete testis and destruction of the surrounding testicular tissue (5). The current consensus among researchers is that TARTs are derived from ectopic adrenal cells that have migrated to the gonad in early fetal life (6,7,8). This hypothesis is in agreement with the findings of the expression in TART of mRNAs that are normally expressed in the adrenal cortex, and that TART cells are able to produce steroid hormones characteristic of the adrenal cortex and Leydig cells (LCs) in the testis (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Due to an intact feedback system with activation of the CRH-ACTH axis, the production of androgens and steroid precursors prior to the enzyme defect is increased [1,2]. Adequate substitution therapy with glucocorticoids and mineralocorticoids is a prerequisite in order to avoid short-term and/or long-term complications such as electrolyte imbalances, addisonian crisis, accelerated bone maturation, short stature, hirsutism and virilization, decreased fertility, obesity, and hypertension [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Although controversial (14,15), male infertility has been described in patients with 21-hydroxylase deficiency. Regarding the underlying mechanism of male infertility in 21-hydroxylase deficient patients, suppression of gonadotropin secretion by increased adrenal steroids due to the untreated deficiency is considered to be the cause of spermatogenesis failure (16), while it has also been suggested that the main cause of infertility in such patients is the presence of testicular adrenal rest tumors, thought to originate from aberrant adrenal tissue (17), which compress the seminiferous tubules, causing obstructive azoospermia (18). In the present two cases, though low serum concentrations of LH and FSH were observed, neither steno-sis nor compression of seminiferous tubules by a testicular tumor was identified, which supports the speculation that the suppression of gonadotropin by increased adrenal androgens due to untreated 21-hydroxylase deficiency may result in sperm dysfunction (19).…”
Section: Discussionmentioning
confidence: 99%